URGENSI PENERAPAN ETIKA BISNIS ISLAM DALAM JUAL BELI ONLINE - Zulaikah, Zulaikah; Sari, Nova Purnama (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
In today's modern era, many business actors do their business by utilizing technological sophistication, such as buying and selling online. However, in practice there are not a few online buying and selling that are carried out with fraud or dishonesty, such as not sending goods when the money has been transferred, sending goods that do not match the description, goods sent have defects. On the consumer side, it is common to find consumers with the COD payment method, unwilling to pay when orders arrive and even canceling orders unilaterally. Therefore it is very important to apply business ethics that can be used as a guide for online buying and selling actors. Business ethics means a set of principles and norms that business people must commit to in transactions, behavior and relationships to achieve their business goals safely and benefit both parties. This study uses a qualitative descriptive method, namely exploring facts and phenomena in depth and then the author analyzes it in the form of descriptive words. The data collection technique was carried out in a triangulation (combined) manner and the analysis in this study used an inductive approach. The results in this study are that the application of Islamic business ethics is very important to be able to encourage online buying and selling to run a business in good ways, not violating existing norms and rules, so that the business being run can continue to exist in the long term and receive blessings from Allah also gives benefit to others. As for the principles that must be applied in Islamic business ethics include honesty, transparency, trustworthiness, selling good quality goods, mutual pleasure, and friendly service. These principles are very important to apply in buying and selling online so that they become the basis for buying and selling behavior online so as not to harm either party.